Elucidation of correlated disorder in zeolite IM‐18. Issue 3 (13th May 2019) - Wang, Xiaoge; Shen, Yihan; Liu, Rongli; Liu, Xiaolong; Lin, Cong; Shi, Dier; Chen, Yanping; Liao, Fuhui; Lin, Jianhua; Sun, Junliang
Abstract : The microstructure of zeolite IM‐18 with correlated disorder was elucidated by simulating the diffuse scattering of powder and single‐crystal diffraction patterns. The method could be applied to other multidimensional disordered structures. Abstract : Classical crystallography is based on the translational periodicity of crystals and the analysis of discrete Bragg reflections. However, it is inadequate for determining disordered structures, of which the diffuse scattering is vital to evaluate the disorder level. The correlated disorder of IM‐18 presents as zigzag chains arranged in translational periodicity and the double four‐ring units randomly distributed along two dimensions. Supercell models regulated by multiple probabilities were systematically built to simulate the single‐crystal and powder X‐ray diffraction patterns in order to ascertain the specific disorder configuration in the single‐crystal or polycrystalline samples of IM‐18. The presence of defects in the polycrystalline sample was proved by combining 29 Si magic angle spinning (MAS) NMR and 1 H– 1 H double quantum MAS NMR spectra, and was quantitatively explored by the simulation method. The method could also elucidate other disordered structures in polycrystalline or single‐crystal samples, despite the presence of defects or multidimensional disorder.